(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study of mange in goat was conducted in Rajshahi district of Bangladesh. It was an attempt to determine the prevalence and the effect of risk factors of mange in goat considering a total of 129 goat rearing farms (containing about a total 1277 numbers of goats) during the period from July’2010 to June’2011. Comparative effects of risk factors like farm size, feeding, season and land topography on the prevalence of mange in goat were measured by logistic regression analysis. Overall prevalence was 5.95% and the prevalence of mange in small, medium and large farms were 4.13%, 6.03% and 9.04%, respectively which was statistically significant (P=0.033). The prevalence was observed 3.61%, 6.03% and 8.25% in good, moderate and poor feedings, respectively and the differences were statistically significant (P=0.044). In case of season, the prevalence of mange was 5.14%, 10.74% and 2.09% in rainy, winter and summer seasons, respectively and the differences among the seasons was statistically highly significant (P=0.000). The prevalence of mange was 8.81%, 5.94% and 3.09% in low, medium and high land, respectively, which were significantly (P=0.022) different among the different land categories. The purpose of this study is mainly concerned with the effects of mange prevalence in goats caused by the different risk factors like farm size, feeding, season and land topography in Rajshahi district of Bangladesh. J Bangladesh Agril Univ 18(1): 101–104, 2020 https://doi.org/10.5455/JBAU.94745